Depressive symptoms in patients with acute coronary syndrome - Mello,Aline Pardo de (2011)
ABSTRACT Objective: To trace an epidemiological profile, to verify presence of depressive symptoms in patients with previous diagnosis of acute coronary syndrome and to identify factors that contribute to maintenance of depressive symptoms in the sample. Methods:A cross-section study carried out at the Cardiology Outpatients Clinics of Universidade Federal de São Paulo. An instrument prepared by the authors was used, which was based on similar studies with patient identification data, questions related to the psychological follow-up, relationship with family members and friends, in addition to use of the Beck Depression Inventory. Methods: A cross-section study carried out at the Cardiology Outpatients Clinics of Universidade Federal de São Paulo. An instrument prepared by the authors was used, which was based on similar studies with patient identification data, questions related to the psychological follow-up, relationship with family members and friends, in addition to use of the Beck Depression Inventory. Results: A total of 200 patients were interviewed, 127 (63.5%) were male. The mean age was 60.19 years with a standard deviation of 9.38, minimum age of 36 years and maximum of 81 years; 164 (82%) denied any follow-up with a psychologist or psychiatrist in the phase after acute coronary syndrome diagnosis and treatment. In the utilization of Beck Depression Inventory, 67 (33.5%) presented scores between 0 and 4, indicating mild depressive symptoms; 72 (36%) had scores between 5 and 9, indicating mild to moderate depressive symptoms, and 61 (30.5%) presented scores greater than 9, which point out moderate to severe depressive symptoms. Conclusion: The evaluation and multiprofessional follow-up can help patients cope with the illness in addition to providing greater compliance to drug therapy and beginning changes in life habits.